Development of a failure assessment methodology for flip chip electronic assembly - Yeo, Alfred Swain Hong. (2008)
In this project, two different solder bump materials are evaluated, they are lead-based 63Sn/37Pb solder and lead-free 96.5Sn/3.5Ag solder. Their solder joint fatigue lives on flip chip on board (FCOB) assembly are assessed by experimental testing and numerical modeling. FCOB assemblies are subjected to a temperature cycle test profile of -40/125°C. Failure analysis is performed to determine the failure mode and failure location. From the flip chip solder joint fatigue data, a two-parameter Weibull analysis is used to derive the mean time to failure (MTTF). Non-linear FE analysis is used to simulate the flip chip solder joint reliability under the temperature cycling loading condition, based on four different solder constitutive models, such as elastic-plastic, elastic-creep, elastic-plastic-creep and viscoplastic analyses.